Culture Indicators in Global Aeronautical Communication - Borowska, Anna Paulina (The ESPecialist, 2020)
Aviation English has been used globally and now is regarded as lingua franca of aviation communication. Communication in any foreign language entails cultural connotations. Moreover, reactions caused by perceived potential misconceptions of one’s cultural or ethnic identity are context-dependent. Aeronautical communication in global context by definition does not belong to any specific culture, so it should be devoid of any cultural elements being effective at the same time. Participants of different cultural groups take part in this type of communication on a regular basis. On the one hand, they are equipped with the tool such as standard phraseology binding in so called routine situations in order to avoid communication breakdown as this specific code seems to go beyond the borders of culture. There is no time for an analysis of who is who, but only for the completion of the mechanical operational tasks. On the other hand, according to the conducted research, it has been observed that the operational interlocutors cannot efficiently escape from their own cultural backgrounds when communicating in both routine and non-routine situations. Therefore, still some differences in cultural perception of conversation partners do exist and influence the aeronautical communication. The article describes the current situation and presents common culture indicators in a selected context. The research shows that without any doubt, and in order to be effective communicators, the airline pilots and air traffic controllers should adopt positive orientation towards their interlocutor’s culture.